A Comprehensive Review on Metal Nanoparticles Produced by Green Synthesis and Their Applications in Glaucoma Treatment - Aravinda Nalla; Dibyalochan Mohanty (Journal of Bio-X Research)
The eye is one of the most delicate organs in the body, and glaucoma is considered to be a major cause of blindness. The unique and distinct architecture and physiology of the human eye continue to pose a major challenge for pharmacologists and researchers seeking to provide effective medication delivery. Despite the number of established invasive and noninvasive eye treatments, such as implants, eye drops, and injections, these still lead to several serious side effects that can result from either low bioavailability or adverse ocular effects. Novel eye disease treatments can be developed with the help of nanoscience and nanotechnology. Many active compounds have been engineered to react with nanocarriers to engage with ocular tissues precisely and overcome ocular difficulties. Future research into novel drug delivery systems and targeted treatments is expected to increase because the approach of reducing intraocular pressure (IOP) cannot contain the progress of glaucoma in the general population of patients. This review focuses on the potential benefits of green chemistry and nanotechnology in ophthalmology, particularly in the treatment and diagnosis of glaucoma. Green synthesis has attracted significant interest as a dependable, environmentally friendly, and sustainable method for producing a range of nanomaterials, such as metal/oxide nanoparticles, hybrid materials, and bioinspired materials.